Immunochromatographic Test over Microscopy in Diagnosis of Severe Malaria in Bangladesh - Awwal, A; Amin, MR; Hafiz, SAMMA; Rahman, M; Ali, M; Sattar, A; Rahman, MR; Faiz, MA (Journal of Armed Forces Medical College, Bangladesh, 2011)
Objective: This study was conducted to determine the advantage of Immunochromatographic test over microscopic peripheral smear in clinically suspected severe malaria. Methods: Total 106 consecutive clinically diagnosed severe malaria cases were enrolled with patients over 12 years of age irrespective of sex, race, religion and pregnancy from March to August 2002, at one medicine unit of Chittagong Medical College Hospital. The immunochromatographic rapid diagnosis test and microscopy were performed in all cases. Results: Sensitivity and specificity of immunochromatographic Paracheck Pf test was found 91.42% and 90.65% in this study. Positive predictive value was 90.56% and negative predictive value was 91.5%. The sensitivity of microscopy was only 69.8%. Conclusion: Reliable quality controlled malaria microscopy is difficult to provide in many rural remote areas due to lack of logistics manpower and electricity facility. Rapid diagnostic test like Paracheck Pf test could be of use in such a situation which is reliable, cheap and easy to perform. Key words: Advantage; immunochromatographic test; microscopic test DOI: http://dx.doi.org/10.3329/jafmc.v7i1.8617 JAFMC Bangladesh. Vol 7, No 1 (June) 2011; 4-7